Photocatalytic inactivation of Escherichia coli bacteria in water using low pressure plasma deposited TiO2 cellulose fabric. Issue 9 (2nd May 2019) - De Vietro, Nicoletta; Tursi, Antonio; Beneduci, Amerigo; Chidichimo, Francesco; Milella, Antonella; Fracassi, Francesco; Chatzisymeon, Efthalia; Chidichimo, Giuseppe
Abstract : Fabrics obtained from cellulose spinning were coated with TiO2 film, through the low pressure plasma sputtering technique, in order to get antibacterial activity. Abstract : Fabrics obtained from cellulose spinning, extracted from Spanish broom, were coated with TiO2 film, through the low pressure plasma sputtering technique, in order to get antibacterial activity. The obtained fabrics were used for the photocatalytic degradation of Escherichia coli, by irradiation with UV-light emitting diodes (UV-LED), in a batch photocatalytic reactor. Before and after functionalization treatments, cellulosic substrates were chemically characterized by X-ray photoelectron spectroscopy (XPS) analyses. Water Contact Angle (WCA) measurements allowed obtaining information about the hydrophilicity of the materials, while their antibacterial efficiency was determined at several initial concentrations (from 10 3 up to 10 8 CFU mL −1 ) of bacteria in distilled water, bottled water and synthetic wastewater. It was found that photocatalytic reactions were capable of achieving up to 100% bacterial inactivation in 1 h of treatment, following a pseudo-first order kinetic model. No bacterial regrowth was observed after photocatalytic treatments in almost all experimental conditions. In contrast, during photolytic treatment ( i.e. in the absence of the TiO2 coated fabrics) bacteria recovered their initial concentration after 3 h in the dark. Finally, the reusability of the plasma modified fibers to inactivate bacteria was studied.